A biomechanical analysis of differences between natural and clinical angle degrees and correlations to performance in road cycling - Aliye Büyükergün; Milaim Berisha (IP Iermakov S.S., 2022)
Background and Study Aim. The study aims to determine differences between natural and clinical angle degrees in hips and shoulders, and determination of the correlations between angle degrees and functional threshold power (FTP) in road cycling athletes. Material and Methods. The study includes 11 male road cycling athletes aged 14-16 years old. The volunteer's body weight average was determined as 68.5±14.58, body height average was 175.4±6.98, and body mass index average 21.8±3.87. Volunteers are active athletes in "Büyükçekmece Road Cycling Team". To measure the performance of the cyclists clinical hip angle, clinical shoulder angle, hip angle degree, shoulder angle, functional threshold power (FTP) tests were used. The Kinovea 0.8.15 program was used in the data analysis of the variables in the study. Analyzes were performed using SPSS 26 analysis program. The analyses of the Shapiro Wilks test resulted in the normal distribution of the variables included in the study.  Correlations between FTP test parameters and angle degrees, the correlation of a continued variable were calculated with Pearson correlation. Results. A statistically significant correlation between functional threshold power parameters such as distance, power avarege, total energy, cadance avarege, speed avarege, functional threshold power, and hip angle degree parameter (p<0.05). Similarly, correlations between functional threshold power, parameters such as power avarege and back curve resulted to be statistically significant (p<0.05). Also, like an functional threshold power parameter, speed avarege resulted to be in a significant correlation with the clinical shoulders angle degree. Conclusions. Based on these results, increases in the FTP parameters may affect positively the cyclist's performance helping to avoid undesirable hip angles, which may lead to back pain. Similarly, power average and back curve degree resulted to be in a correlation. Therefore, the back curve degree may be increased or decreased by the changes in the power average parameter.  In addition, during the high intensity of training and fatigue levels increased, the clinical hip and shoulder angles were also increased.